Peptide receptor radionuclide therapy in patients with medullary thyroid carcinoma: predictors and pitfalls - Carolien M. Beukhof (BMC Cancer, 2019)
Abstract Background For progressive metastatic medullary thyroid carcinoma (MTC), the available treatment options with tyrosine kinase inhibitors result in grade 3–4 adverse events in a large number of patients. Peptide Receptor Radionuclide Therapy (PRRT), which has also been suggested to be a useful treatment for MTC, is usually well tolerated, but evidence on its effectivity is very limited. Methods Retrospective evaluation of treatment effects of PRRT in a highly selected group of MTC patients, with progressive disease or refractory symptoms. In addition, a retrospective evaluation of uptake on historical 111In-DTPA-octreotide scans was performed in patients with detectable tumor size > 1 cm. Results Over the last 17 years, 10 MTC patients were treated with PRRT. Four out of 10 patients showed stable disease at first follow-up (8 months after start of therapy) whereas the other 6 were progressive. Patients with stable disease were characterized by a combination of both a high uptake on 111In-DTPA-octreotide scan (uptake grade ≥ 3) and a positive somatostatin receptor type 2a (SSTR2a) expression of the tumor by immunohistochemistry. Retrospective evaluation of historical 111In-DTPA-octreotide scans of 35 non-treated MTC patients revealed low uptake (uptake grade 1) in the vast majority of patients 31/35 (89%) with intermediate uptake (uptake grade 2) in the remaining 4/35 (11%). Conclusions PRRT using 177Lu-octreotate could be considered as a treatment in those patients with high uptake on 111In-DTPA-octreotide scan (uptake grade 3) and positive SSTR2a expression in tumor histology. Since this high uptake was present in a very limited number of patients, this treatment is only suitable in a selected group of MTC patients.